Area de actividad y uso del habitat de dos venados cola blanca (Odocoileus virginianus) en un bosque tropical de la costa de Jalisco, México - Sánchez Rojas, Gerardo; Gallina, Sonia; Mandujano, Salvador (Instituto de Ecología, A.C., 1997)
Behavioral and habitat use patterns ot white tailed deer (Odocoileus virginianus) by radio trackiny two individuáis, an adult female and subadult male, in a tropical deciduous forest at The Chamela Biological Station in Jalisco, México, is described the study was carried out from 1992 to 1994. Tho female was monitoried in two dry and two wet seasons. Dunng tho dry season her home lange size was 11 ha and moving distances varied from 1.44 to 1.48 km The distances in dry season by the femai'e show larger displacemrnt during crepuscular hours. In the wet season home tange is larger (21 and 34 ha) as well as daily distances (1.98 and 2.58 km), These distances kept constant along the day, probably due to tho search of more plant spocies diversity that enrich the quality of the diet. In both seasons, distances recorded by the female during night decrease in cornparision with day displacernents. The male was oniy monitored in the dry season, using a larger home range (26 ha) and movyng more distances (2.5 km) That the female probably to satisfy his eneigetic requirements. The female used more intensely tho slopes,